Main aspects of the development of quality design of educational materials - Bondarenko, Sofia; Fomin, Volodymyr (Professional Art Education, 2023)
The article analyzes the available theoretical and practical experience in the field of pedagogical design, in particular, the main aspects of the development of high-quality design of educational materials for various target children’s audiences. Methods & methodology. The article uses theoretical methods: comparison, systematization and generalization of scientific sources. The practical principles of creating educational materials and environment, based on the psychological and physiological characteristics of perception by children of different age categories, are highlighted. Among them, the use of a visual series of educational materials in electronic pedagogical presentations is special. The scientific novelty of the article lies in the coverage and practical implementation of modern design technologies for the creation of educational and pedagogical materials for effective perception by children of different age categories due to the influence of the quality of multimedia educational materials on the assimilation of knowledge. Results. The importance of logical and consistent presentation of new information, as well as the need to optimize and update educational materials, is considered. The importance of typography in educational design is emphasized, as a good choice of font can improve the readability of the text, highlight important information and promote interest in learning, and color gamut, use of photos and video materials. The differences in design for different age categories are characterized, considering the level of knowledge and motivation of the target audience. The importance of the choice of colors in educational design is highlighted, considering their influence on the mood and behavior of users, and techniques for the successful selection of a color range are given. Ways of using color, typography and multimedia materials to improve students’ perception and assimilation of new information have been identified. In further work, it is planned to analyze and specify various material and technical means for designing educational materials and to develop a series of educational school posters with the help of modern graphic editors.